Phytovesicular Nanoconstructs for Advanced Delivery of Medicinal Metabolites: An In-Depth Review - Pandey, Vishal; Rathee, Sunny; Sen, Debasis; Jain, Sanjay K.; Patil, Umesh K. (Current Drug Targets, 2024)
Phytochemicals, the bioactive compounds in plants, possess therapeutic benefits, such as antimicrobial, antioxidant, and pharmacological activities. However, their clinical use is often hindered by poor bioavailability and stability. Phytosome technology enhances the absorption and efficacy of these compounds by integrating vesicular systems like liposomes, niosomes, transfersomes, and ethosomes. Phytosomes offer diverse biological benefits, including cardiovascular protection through improved endothelial function and oxidative stress reduction. They enhance cognitive function and protect against neurodegenerative diseases in the nervous system, aid digestion and reduce inflammation in the gastrointestinal system, and provide hepatoprotective effects by enhancing liver detoxification and protection against toxins. In the genitourinary system, phytosomes improve renal function and exhibit anti-inflammatory properties. They also modulate the immune system by enhancing immune responses and reducing inflammation and oxidative stress. Additionally, phytosomes promote skin health by protecting against UV radiation and improving hydration and elasticity. Recent patented phytosome technologies have led to innovative formulations that improve the stability, bioavailability, and therapeutic efficacy of phytochemicals, although commercialization challenges like manufacturing scalability and regulatory hurdles remain. Secondary metabolites from natural products are classified into primary and secondary metabolites, with a significant focus on terpenoids, phenolic compounds, and nitrogen-containing compounds. These metabolites have notable biological activities: antimicrobial, antioxidant, antibiotic, antiviral, anti-inflammatory, and anticancer effects. In summary, this review amalgamates the latest advancements in phytosome technology and secondary metabolite research, presenting a holistic view of their potential to advance therapeutic interventions and contribute to the ever-evolving landscape of natural product-based medicine.
Keywords: secondary metabolites